Nicotine dependence phenotype and lung cancer risk - Muscat, Joshua E. (2011)
BACKGROUND: A behavioral phenotype that characterizes nicotine dependence, the time to first cigarette after waking, is hypothesized to increase the risk of lung cancer. METHODS: A case-control study of histologically-confirmed lung cancer was conducted. The current analysis included 4775 lung cancer cases and 2835 controls who were regular cigarette smokers. RESULTS: Compared to subjects who smoked more than 60 minutes after waking, the pack-years -adjusted odds ratio was 1.31 (95% confidence intervals [CI] 1.11–1.54) for subjects who smoked 31–60 minutes after waking and 1.79 (95% CI 1.56–2.07) for subjects who smoked within 30 minutes. The risk estimates were similar when smoking was modeled as total years, smoking status (current vs. former), cigarettes per day, years since quitting, and excess odds ratio. The findings were consistent for all histologic types of lung cancer. CONCLUSION: These findings indicate that a specific nicotine dependence phenotype that is associated with the amount of smoke uptake per cigarette is independently associated with lung cancer risk. The findings may help identify high risk individuals who would benefit from targeted interventions.